2015
DOI: 10.1007/s11739-014-1183-3
|View full text |Cite
|
Sign up to set email alerts
|

FGF-23 levels in patients with critical carotid artery stenosis

Abstract: The aim of this study was to evaluate fibroblast growth factor (FGF)-23 serum levels and its tissue expression in patients with critical carotid artery stenosis (CAS). We selected 35 patients with critical CAS undergoing carotid thromboendoarterectomy. In each patient, FGF-23 serum levels were evaluated just prior to the surgery (t0) and 30 min (t1) thereafter. Moreover, macrophage cytokines were measured at baselines. Carotid artery specimens were used for immune histochemistry. On the basis of the histology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…7D). Treatment with either the cell-permeable or non–cell-permeable C5aR1 inhibitor reduced the production of fibroblast growth factor (FGF), a hallmark growth factor of macrophages in advanced atherosclerotic lesions ( 48 , 49 ). This observation may indicate that the surface C5aR1 activity of macrophages in plaques serves a specific function connected to FGF biology (fig.…”
Section: Resultsmentioning
confidence: 99%
“…7D). Treatment with either the cell-permeable or non–cell-permeable C5aR1 inhibitor reduced the production of fibroblast growth factor (FGF), a hallmark growth factor of macrophages in advanced atherosclerotic lesions ( 48 , 49 ). This observation may indicate that the surface C5aR1 activity of macrophages in plaques serves a specific function connected to FGF biology (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Del Porto et al. detected FGF-23 inside the atherosclerotic plaque after endarterectomy and plaque immunohistochemistry ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that the preoperative FGF-23 level was independently correlated with a higher cumulating MACCE rate; meanwhile, the FGF-23 level at discharge showed a trend to be positively associated with the cumulative MACCE rate but did not reach statistical significance. The possible explanations could be that FGF-23 might facilitate the progression of atherosclerosis through several methods including regulating oxidative stress and proliferation of vascular endothelial cells, as well as promoting the infiltration of macrophages ( 18 , 20 , 25 , 26 ). Therefore, preoperative FGF-23 could directly induce the incidence of MACCE.…”
Section: Discussionmentioning
confidence: 99%